Human Computer Interaction and Emerging Technologies: Workshop Proceedings from the INTERACT 2019 Workshops - (:unkn) unknown (My University, 2026)
Human Computer Interaction and Emerging Technologies Workshop Proceedings from the INTERACT 2019 Workshops